SUPERCRITICAL EXTRACTION OF LYOPHILIZED STRAWBERRY ANTHOCYANINS WITH PULSED ELECTRIC FIELDS PRETREATMENT - Marco A. Ávila-Hernández; César Pérez-Alonso; Juan Orozco-Villafuerte; Carlos E. Barrera-Díaz; Erik Alpizar-Reyes; Julian Cruz-Olivares (Química Nova, 2022)
The lyophilized strawberry anthocyanins were extracted using a supercritical extraction (SE) process. The effect of pulsed electric fields (PEF) as pretreatment and the influence of the addition of ethanol as a cosolvent on the percentage of extraction yield (EY) and the total anthocyanin concentration (TAC) were analyzed. The effect of PEF was evaluated at 0.5 and 1.0 kV/cm, while the effect of the cosolvent was studied in mixtures of supercritical carbon dioxide - ethanol (SCCO2 + ethanol) at 1.6 and 3.3% by weight. The best results (% EY = 0.506, TAC = 0.428 g /100 g of lyophilized strawberry) were obtained with a PEF pretreatment of 1.0 kV cm-1, 3.3%wt. ethanol at 200 bar and 333.15 K. The experimental results of solubility were suitably adjusted with the Kumar and Johnston model. The maximum solubility (0.114 g/100 g of solvent mixture) was obtained at 300 bar and 313.15 K.